Physical Fitness is a Mediator in the Relationship between Arterial Stiffness and Cognitive Function - Alinne Nascimento; Duarte Barros; José Oliveira; Joana Carvalho; Lucimere Bohn (Artery Research, 2019)
Background: To investigate physical fitness as a mediator of the relationship between arterial stiffness and cognitive function in seniors. Methods: This is a cross-sectional study comprising 155 individuals free from chronic diseases (75.5 ± 6.5 years; 69.7% female). Carotid-femoral pulse wave was assessed through applanation tonometry. Cognitive function was evaluated with Montreal Cognitive Assessment (MoCA). Physical fitness was assessed through handgrip strength and Senior Fitness Test (SFT). A Z-score including individual physical fitness components was computed as a global index of physical fitness. Hayes’s PROCESS macro for Statistical Package for the Social Sciences was used for the simple mediation analysis, using bootstrapped procedures. Results: After adjustments for sex and age, physical fitness Z-score mediated the relationship between arterial stiffness and cognitive function [Indirect effect = −0.382 (95% CI −0.670 to −0.138)]. Conclusion: Findings suggest that physical fitness, independently of sex and age, is a mediator on the relationship between arterial stiffness and cognitive function in seniors free from chronic diseases.